Physically engineered extracellular vesicles targeted delivering miR-21-5p to promote renoprotection after renal ischemia-reperfusion injury - Di Wu; Wenjie Ma; Liucheng Wang; Chengcheng Long; Silin Chen; Jingyu Liu; Yiguan Qian; Jun Zhao; Changcheng Zhou; Ruipeng Jia (Materials Today Bio)
Acute kidney injury (AKI) resulting from ischemia-reperfusion injury (IRI) is a common challenge in various clinical practices, yet effective therapies remain elusive. Endothelial injury plays a crucial role in the pathogenesis of renal IRI. Endothelial progenitor cells (EPCs) derived extracellular vesicles (EVs) hold promise as cell-free therapies for treating renal IRI; however, their efficacy is limited by low delivery efficiency. In this study, we developed neutrophils (NEs) membrane-modified EVs (N-EVs) by exploiting the natural properties of NEs to target damaged endothelium. N-EVs inherited the characteristic membrane proteins of NEs along with the biological functions of EPCs-EVs. Results from in vitro and in vivo experiments demonstrated that N-EVs significantly enhanced the targeting efficiency of EVs towards IRI kidneys via P-selectin glycoprotein ligand-1 (PSGL-1). Moreover, N-EVs effectively promoted the proliferation, migration, and tube-formation abilities of injured endothelial cells (ECs) and contributed to overall renal function improvement in IRI kidneys through targeted delivery of miR-21-5p. Additionally, N-EVs could restore damaged endothelial integrity, reduce cytokine release, and inhibit leukocyte infiltration, hence alleviating renal inflammation. In conclusion, our accessible engineering approach represents a promising strategy for treating renal IRI. Furthermore, this membrane hybrid modification can be tailored and optimized for broader applications in treating other diseases.